Information Security Practice and Experience 10th International Conference, ISPEC 2014, Fuzhou, China, May 5-8, 2014, Proceedings - Huang, Xinyi; Zhou, Jianying (Security and Cryptology, 2014)
This book constitutes the proceedings of the 10th International Conference on Information Security Practice and Experience, ISPEC 2014, held in Fuzhou, China, in May 2014. The 36 papers presented in this volume were carefully reviewed and selected from 158 submissions. In addition the book contains 5 invited papers. The regular papers are organized in topical sections named: network security; system security; security practice; security protocols; cloud security; digital signature; encryption and key agreement and theory.